Rapid Deployment Aortic Valves Deliver Superior Hemodynamic Performance in Vitro. Issue 5 (September 2017) - Ai, Lisong; Chen, Harvey; Lin, Virginia; Bapat, Vinayak N.
Objective: Clinical studies have demonstrated excellent hemodynamic performance of rapid deployment aortic valves; however, few studies have directly compared the performance of these valves with conventional bioprosthetic valves. Thus, the hemodynamic function of the EDWARDS INTUITY valve (rapid deployment valve) was compared with the Edwards Magna Ease valve in vitro (Edwards Lifesciences Corp, Irvine, CA USA). Methods: Elastomeric material was used to create an aortic root model that included a left ventricular outflow tract and aortic annulus. The model was based on reconstructions from 3-dimensional multislice computed tomography images in patients with aortic stenosis; the aortic root was scaled to a 21-mm effective annulus diameter. EDWARDS INTUITY valves (21-mm diameter) were deployed by stent frame expansion within the aortic root; Edwards Magna Ease valves (21-mm diameter) were sutured to the annulus. The left ventricular outflow tract area index (left ventricular outflow tract area/baseline area) and ellipticity or noncircularity as indexed by Dmax /Dmin were measured under a video microscope after valve placement. Hemodynamic data were collected under pulsatile flow with saline (70 beats per minute, 5 L/min, 100 mm Hg aortic pressure). Results: Compared with the Edwards Magna Ease valve (n = 4), the EDWARDS INTUITY valve (n = 4) had a greater effective orifice area (1.56 ± 0.01 vs 1.85 ± 0.06 cm 2, P < 0.001) and a lower transvalvular pressure gradient (23.4 ± 0.51 vs 16.8 ± 1.3 mm Hg, P < 0.001). Multiple regression analysis showed that 93% of the variation in the effective orifice area and transvalvular pressure gradient was due to variation in the left ventricular outflow tract area index and ellipticity index. Conclusions: A clinically relevant aortic root model was developed to evaluate aortic valve performance. The superior performance of the EDWARDS INTUITY valve seemed to be related to both a greater inflow area and a more circular left ventricular outflow tract.